O processo de auto-avaliação institucional como gerador e disseminador de conhecimentos estratégicos para as IES - Santos, Rosana Brito (2014)
The present dissertation aims to present the institutional self-assessment conducted by the own assessment Committees (CPA´s), as a generating and disseminating knowledge tool that can help in the process of making strategic decisions on the part of Higher Education Institutions (IES). The approach chosen was the exploratory research. Based on the literary review of national and international authors to meet and analyze more deeply the concepts of institutional self-assessment, organizational strategy, knowledge management and organizational learning. From this point, it was possible to construct arguments capable of enabling the attainment of the objective proposed. At the end of the work it could be noted that the process of institutional self- assessment conducted annually by the CPAs can, in fact, generate knowledge which are able to potentiate the taking of strategic actions on the part of the IES.